Recent Advances in the Use of Ganoderma lucidum and Coriolus versicolor Mushrooms to Enhance the Anticancer Efficacy of EGFR-Targeted Drugs in Lung Cancer - Hang Zhang; Longling Wang; Yuet Wa Chan; William C. Cho; Zhong Zuo; Kenneth K. W. To (Pharmaceutics)
Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) is the major subtype, accounting for more than 85% of all lung cancer cases. Recent advances in precision oncology have allowed NSCLC patients bearing specific oncogenic epidermal growth factor receptor (EGFR) mutations to respond well to EGFR tyrosine kinase inhibitors (TKIs). Due to the high EGFR mutation frequency (up to more than 50%) observed particularly in Asian NSCLC patients, EGFR-TKIs have produced unprecedented clinical responses. Depending on their binding interactions with EGFRs, EGFR-TKIs are classified as reversible (first-generation: gefitinib and erlotinib) or irreversible inhibitors (second-generation: afatinib and dacomitinib; third-generation: osimertinib). While the discovery of osimertinib represents a breakthrough in the treatment of NSCLC, most patients eventually relapse and develop drug resistance. Novel strategies to overcome osimertinib resistance are urgently needed. In Asian countries, the concomitant use of Western medicine and traditional Chinese medicine (TCM) is very common. Ganoderma lucidum (Lingzhi) and Coriolus versicolor (Yunzhi) are popular TCMs that are widely consumed by cancer patients to enhance anticancer efficacy and alleviate the side effects associated with cancer therapy. The bioactive polysaccharides and triterpenes in these medicinal mushrooms are believed to contribute to their anticancer and immunomodulating effects. This review presents the latest update on the beneficial combination of Lingzhi/Yunzhi and EGFR-TKIs to overcome drug resistance. The effects of Lingzhi/Yunzhi on various oncogenic signaling pathways and anticancer immunity, as well as their potential to overcome EGFR-TKI resistance, are highlighted. The potential risk of herb–drug interactions could become critical when cancer patients take Lingzhi/Yunzhi as adjuvants during cancer therapy. The involvement of drug transporters and cytochrome P450 enzymes in these herb–drug interactions is summarized. Finally, we also discuss the opportunities and future prospects regarding the combined use of Lingzhi/Yunzhi and EGFR-TKIs in cancer patients.